2023
DOI: 10.7717/peerj.15012
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of the predictors of multidrug resistance and methicillin resistance among Staphylococcus spp. isolated from canine specimens submitted to a diagnostic laboratory in Tennessee, USA

Abstract: Background Understanding drivers of multidrug resistance (MDR) and methicillin resistance, which have increased among canine staphylococcal isolates, is essential for guiding antimicrobial use practices. Therefore, the objective of this study was to identify predictors of MDR and methicillin resistance among Staphylococcus spp. commonly isolated from canine clinical specimens. Methods This retrospective study used records of canine specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…In this study, the highest prevalence of MRS was observed in dog S. pseudintermedius (37% and 33.3% in commensal and infection-causing isolates, respectively). Similar results were reported in a study conducted in Tennessee (USA), where 30.8% of the isolates were MRSP [52].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the highest prevalence of MRS was observed in dog S. pseudintermedius (37% and 33.3% in commensal and infection-causing isolates, respectively). Similar results were reported in a study conducted in Tennessee (USA), where 30.8% of the isolates were MRSP [52].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been observed in other studies conducted in the Iberian Peninsula [ 51 ] and Canada [ 53 ]. However, lower AMR profiles were observed in another study conducted in the USA [ 52 ]. In some Scandinavian countries, the main resistance observed was to penicillins in different proportions, with 65% in Denmark [ 54 ], ≈70% in Finland [ 55 ], 14% in Norway [ 56 ], and 19.5% in Sweden [ 57 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation